2002
DOI: 10.1023/a:1021272519714
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The influence of ultraviolet photolysis as a pretreatment to the aerobic and anaerobic biological mineralization of a 14C-polyacrylamide was assessed using a series of radiorespirometry bioassays. The polyacrylamide studied was non-ionic with molecular weights ranging between 100,000 and 1 million. Aerobic and anaerobic biomineralization of the unphotolysed (raw) polyacrylamide was found to be only 0.60% and 0.70%, respectively, after 6 weeks of incubation, and hence indicative of the natural recalcitrance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Previous study has shown that molecular weights above 3 Â 10 3 Da was recalcitrant to microbial mineralization (El-Mamouni et al, 2002). Previous study has shown that molecular weights above 3 Â 10 3 Da are recalcitrant to microbial mineralization (El-Mamouni et al, 2002). In addition, although Bacillus (Bao et al, 2010), Acinetobacter (Matsuoka et al, 2002), Pseudomonas (Yu et al, 2015), and Clostridium (Ma et al, 2010) grew in the four reactors, their abundances were low.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Previous study has shown that molecular weights above 3 Â 10 3 Da was recalcitrant to microbial mineralization (El-Mamouni et al, 2002). Previous study has shown that molecular weights above 3 Â 10 3 Da are recalcitrant to microbial mineralization (El-Mamouni et al, 2002). In addition, although Bacillus (Bao et al, 2010), Acinetobacter (Matsuoka et al, 2002), Pseudomonas (Yu et al, 2015), and Clostridium (Ma et al, 2010) grew in the four reactors, their abundances were low.…”
Section: Discussionmentioning
confidence: 82%
“…PAM has been reportedly broken down by physical-chemical factors, including sunlight, chemical, mechanical, and thermal degradation (Caulfield et al, 2002;El-Mamouni et al, 2002). Since the Anaerobic 55 C system was most efficient in the degradation of PAM (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assisted bioremediation techniques that involve synergy between physical, chemical, and biological methods have been tested for AP waste treatment. Some of them include photodegradation by UV radiation (El-Mamouni et al 2002), oxidation with the Fenton reagent (Zhang et al 2019), or with zerovalent iron/EDTA/air (Lu and Wei 2011), as a pretreatment for aerobic or anaerobic biological process. In most cases, pretreatment improves AP solubilization by reducing Mw; thus, hybrid technologies increase AP removal rates and enhance mineralization.…”
Section: Fungal Enzymesmentioning
confidence: 99%
“…For example, PAM from soil or oilfield wastewater can be hydrolyzed as a nitrogen (i.e., amide hydrolysis) or carbon (i.e., carbon chain hydrolysis) source during an aerobic or anaerobic process. Similarly, Haveroen et al 16 , El-Mamouni et al 17 and Nakamiya et al 18 reported that PAM from sewage sludge could be hydrolyzed as a carbon or nitrogen source during an anaerobic or aerobic process ( Table S1 , Supplementary Information). However, several studies revealed that PAM from sewage sludge or riverbed mud might be difficult to hydrolyze during an anaerobic or aerobic process 15 19 .…”
mentioning
confidence: 99%